3d Analysis of Lift and Moment Adaptation via Control Surface Deployments on a 5 MW Wind Turbine Blade. Issue 5 (October 2013) - Agarwala, Ranjeet; Ro, Paul I.
This paper investigates the impact of deploying control surfaces on a model 5 MW offshore wind turbine blade. The wind turbine blade is modeled in 3D based on NREL's 5 MW wind turbine and incorporates varying airfoil shapes and structural twist along the blade length. Lift and aero-dynamic moment at various angle of attack settings are simulated and analyzed. Partial span-wise trailing-edge 3D control surfaces are modeled, simulated and analyzed at various control angles. Results depict the onset of stall around 22 degrees and a larger lift gain versus 10–15 degrees for standard 2D airfoils. Mid-flap controller enhances lift by a factor 2 and mitigates moment a factor of around 7 while end-flap controller enhances lift by a factor of around 1.024 and mitigates moment by a factor of around 2. The results and comparisons obtained serve as one of many instruments for gauging, designing, analyzing, and optimizing wind turbine systems.